PENILAIAN POTENSI DAYA TARIK DANAU BEKAT UNTUK OBJEK WISATA DI KECAMATAN TAYAN HILIR KABUPATEN SANGGAU - yuda, Mah; Said, Syafruddin; anto, Eri (JURNAL HUTAN LESTARI, 2013)
Tayan Downstream is one of the District that is located in Regency Sanggau, West Borneo. In the Tayan Downstream there are several Lakes that each has its own potential, one of which is Lake Bekat. In the Tayan Downstream there are several Lake sthate ach has its own potential,one of which is Lake Bekat. In Lake Bekat there are many types of fishe specially the most prominent is Toman (Orheichepalus micropeltes), Kerandang (Ophiocephalus pleurophthamus) and Biawan (Hellostomata temincki). With the vastexpanse of nature through out the area + 2136.52 Ha and the beautiful scenery around the Lake,Because in the absence of Tayan Downstream nature associated with water attractions (Lake) there should be an assessment of the potential for tourist attraction on Lake Bekat. This study aims to identify andassess the potential attractiveness Lake Bekat to be developed as a tourist attractionand from this study are expected to provide information about the potential value for development Lake Bekat attractions. Thi sresearch uses descriptive methods and techniques of data collection in the field using the method of observation.From theresults of the study obtaineda value of135.98.This value is multiplied by the weighting criteria appeal to the area that is 6so135.98 x 6=815.9 or C. From the research, the need for cooperation with relevant institutions in order to in crease the potential values??in Lake Bekat and the need for status determination so as not to conflicttareas in the future. Key words : Lake, Lake Bekat, Attraction, Tayan Downstream